MODERN MECHANISMS OF PUBLIC ADMINISTRATION IN THE SPHERE OF THE NATIONAL DEFENSE INDUSTRY OF UKRAINE - Marutіan Rena; Vereshchak, Oleksandr (Public Management and Policy, 2025)
The article considers modern mechanisms of public administration in the sphere of the national defense industry of Ukraine. The authors note that public administration in the sphere of the national defense industry of Ukraine is an important element of ensuring national security and defense capability of the country. In this regard, effective management of this sphere is of particular importance in the context of rapid changes in the geopolitical situation and growing threats to national defense. The defense-industrial complex is an important element of state security and economic growth, as it ensures the production of equipment and weapons for the Armed Forces and promotes the development of industry and investment attraction. In the strategic context, the defense industry is an important element of state security, since the effective functioning of this industry makes it possible to ensure military superiority in the international arena. The introduction of modern defense technologies strengthens defense capability and helps increase competitiveness in global arms markets. The authors emphasize the importance of developing and modernizing national standards that must meet international requirements, which allows integrating the defense industry into global markets. The article emphasizes the role of the state defense order as the main tool for ensuring defense needs and stimulating the development of national production. The authors state that the development of public-private partnership is an important factor for attracting the private sector to the modernization of defense capabilities and the introduction of the latest technologies. The study determined that integration into international military-technical projects allows strengthening the country's defense capability and expanding its economic opportunities. The article noted that the development of the defense-industrial complex is also facilitated by the creation of information and analytical systems that ensure informed decision-making and management. As a result, it is important to continue improving the institutional framework, which will ensure the sustainable development of the defense industry of Ukraine and its integration into the international context.